212k views
4 votes
Micah solves a linear equation and concludes that x = 0 is the solution. His work is shown below. (1 – 3x) = 4(– + 2) 4 lines of math. The first line is, StartFraction 5 Over 6 EndFraction left-parenthesis 1 minus 3 x right-parenthesis equals 4 left-parenthesis negative StartFraction 5 x Over EndFraction plus 2 right-parenthesis. The second line is, StartFraction 5 Over 6 EndFraction minus StartFraction 5x Over 2 EndFraction equals StartFraction 5x Over 2 EndFraction plus 8. The third line in plus StartFraction 5x Over 2 EndFraction and StartFraction 5x Over 2 EndFraction on both sides of the equal sign. The fourth line is 0 equals x. 0 = x

2 Answers

3 votes

Answer:

A. Micah’s solution is wrong. There are no values of x that make the statement true.

Explanation:

User Haferblues
by
6.2k points
2 votes

Answer:

Micah's solution is wrong

Explanation:

Micah solves a linear equation and concludes that x = 0 is the solution. His work is shown below.

(1 – 3x) = 4(– + 2)

0 = x

Which statement is true about Micah’s solution?

Micah’s solution is wrong.

There are no values of x that make the statement true.

Micah’s solution is correct, and the value of x that makes the statement true is 0.

Micah should have divided by .

Micah should have subtracted

Solution

First solve for the value of x

Given

(1 – 3x) = 4(– + 2)

It could mean; (1 – 3x) = 4(+ 2)

or

(1 – 3x) = 4(-2)

In the first option (1 – 3x) = 4(+ 2)

1 – 3x = 4(+ 2)

1-3x= 8

-3x=8-1

-3x=7

x= -7/3

In the second option

(1 – 3x) = 4(-2)

1-3x= -8

-3x= -8-1

-3x = -9

x= 3

x= 3 0r -7/3

The values of x that make the statement true are 3 and -7/3

Micah's solution of x=0 is wrong

User Vanity
by
6.3k points